Implementasi Pengembangan Manajemen Perubahan Sekolah di SMPN 3 Banguntapan - Setiawan, Farid; Septiana, Widya; Amalia, Mukhlisatinnisa; Saputri, Rizka Maulina; Nihayah, Nafi’atun (MASALIQ, 2022)
From time to the school certainly evaluates management,changes in management provide room for improvement in aspect that are felt to be further improved in order to achieve the goals of the desired school vision and mission. The author’s goal is to determine the management of change in SMPN 3 Banguntapan while in data collection, the author uses a qualitative approach. The type of research used is library research, that is case studies are an intensive with school principals, where the principal’s role as a driver of renewal is assisted by other school residents making SMPN 3 Banguntapan a school that can facing all challenges in making changes for the better, this can certainly be seen from the spirit of conducting more optimal performance evaluations, so that changes in management that are continuously improved such as in the fields of curriculum, learning, educators, students, and infrastructure will have a positive impact desired school progress.